Study on morpho- anatomical and phytochemical characterization of euphorbia helioscopia l. In doon valley, uttarakhand - MANEESHA SINGH; MOHD ISFAQ (International Journal of Pharma and Bio Sciences, 2017)
Euphorbia helioscopia L. is an annual medicinal plant commonly grown as weeds during winter season, used in folk medicine of various countries around the world. The present studies deals with morphological and anatomical characterization of various plant parts along with determination of its phytoconstituents. Morphological characterization is based on vegetative and reproductive traits such as plant height, number of branches, leaf shape, size and floral characters. The shape of the leaf was found to be oval, broad near the tip and toothed margins. The anatomical studies revealed that in the transverse section of root, it was encircled by cork cells. The phelloderm was 6-8 layered, cortex parenchymatous, well developed endodermis with phloem narrow and wide xylem. In the center, radially arranged vessels and tracheids, uniserrated to multiserrated medullary rays were present and extend up to phloem. The transverse section of stem showed the presence of epidermis covered by a thick layered cuticle. Cortex was parenchymatous and contained laticiferous canals. The phloem was narrow and also contain laticiferous canals. Cambium is present between the xylem and phloem. Xylem is radially arranged and uniserrated to multiserrated medullary rays are present. The presence of sunken stomata in the lower surface of leaf showed its potential to withstand drought environment. A number of secondary metabolites have been reported from sun spurge plant including alkaloids, flavonoids, cardiac glycosides, carbohydrates, saponins, tannins and triterpinoids revealing that this plant can be used in future for finding various biological potential like antimicrobial and antioxidant activities etc.